PENGARUH TEMPAT MINUM NIPPLE DAN PARALON TERHADAP AWAL PRODUKSI FASE GROWER AYAM PETELUR - Wahyu Kolifah (AVES: Jurnal Ilmu Peternakan, 2017)
The research aimed to defermine the effect of nipple and paralon drinking place on start production of growing period laying hens. This research was in Wahyu farm during 2 month. The 300 laying hens and 13 week were used in the trial. The laying hens divided into 2 group using the t-test. The treatment whice are nipple and paralon drinking place. The parameter abserved feed intake, ADG (Average Daily Gain), HDP (Hen Day Production), egg weight, and FCR (Feed Convertion Ratio).The result showed that nipple and paralon drinking place were significanty (P<0.05) on feed intake, ADG (Average Daily Gain), HDP (Hen Day Production), egg weight, and FCR (Feed Convertion Ratio). It ’s suggested to do paralon drinking place on lower capacity farm. Keyword: Feed Intake, ADG, Hen Day Production, Egg Weight and FCR